Preeclampsia 2012. (11th July 2012) - Eiland, Elosha; Nzerue, Chike; Faulkner, Marquetta
Abstract : Preeclampsia is a common complication of pregnancy associated with high maternal morbidity and mortality and intrauterine fetal growth restriction. There is extensive evidence that the reduction of uteroplacental blood flow in this syndrome results from the toxic combination of hypoxia, imbalance of angiogenic and antiangiogenic factors, inflammation, and deranged immunity. Women treated for preeclampsia also have an increased risk for cardiovascular and renal disease. At present it is unclear if the increased cardiovascular and renal disease risks are due to residual and or progressive effects of endothelial damage from the preeclampsia or from shared risk factors between preeclampsia and cardiac disease. Moreover, it appears that endothelin-1 signaling may play a central role in the hypertension associated with preeclampsia. In this paper, we discuss emerging data on the pathogenesis of preeclampsia and review therapeutic options.